Caste system, untouchability, and the depressed - Kotani, Hiroyuki, 1942- (New Delhi : Manohar Publishers & Distributors, 1997)
On India; articles selected from a Japanese text and translated into English.
Includes bibliographical references.
Keywords: Sociology